2017
DOI: 10.1002/jclp.22499
|View full text |Cite
|
Sign up to set email alerts
|

Severity of Suicidal Ideation Matters: Reexamining Correlates of Suicidal Ideation Using Quantile Regression

Abstract: Our findings indicated that predictors of suicidal ideation differed in magnitude at varying levels of suicidal ideation. Implications, limitations, and future research directions are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
1
9
1
Order By: Relevance
“…This pattern of findings may help to clarify a mixed literature on the relationship between BPD and prolonged distress recovery (e.g., Feliu-Soler et al, 2013;Fitzpatrick & Kuo, 2015;Gratz et al, 2010;Jacob et al, 2009;Scheel et al, 2013): positive findings may reflect instances in which ruminative responses were deployed. Though less consistently linked to distress, psychopathology, and other negative outcomes than the brooding component of depressive rumination (e.g., Johnson et al, 2016;Rogers & Joiner, 2018;Treynor et al, 2003), the salubrious effect of self-reflection observed in this study suggests a potential adaptive value of self-focused attention. Further, our findings have treatment implications, as a number of interventions have been shown to reduce ruminative tendencies (Querstret & Cropley, 2013;Watkins et al, 2007), which are easier to modify than facets of personality (Magidson, Roberts, Collado-Rodriguez, & Lejuez, 2014).…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This pattern of findings may help to clarify a mixed literature on the relationship between BPD and prolonged distress recovery (e.g., Feliu-Soler et al, 2013;Fitzpatrick & Kuo, 2015;Gratz et al, 2010;Jacob et al, 2009;Scheel et al, 2013): positive findings may reflect instances in which ruminative responses were deployed. Though less consistently linked to distress, psychopathology, and other negative outcomes than the brooding component of depressive rumination (e.g., Johnson et al, 2016;Rogers & Joiner, 2018;Treynor et al, 2003), the salubrious effect of self-reflection observed in this study suggests a potential adaptive value of self-focused attention. Further, our findings have treatment implications, as a number of interventions have been shown to reduce ruminative tendencies (Querstret & Cropley, 2013;Watkins et al, 2007), which are easier to modify than facets of personality (Magidson, Roberts, Collado-Rodriguez, & Lejuez, 2014).…”
Section: Discussioncontrasting
confidence: 56%
“…Further, our findings have treatment implications, as a number of interventions have been shown to reduce ruminative tendencies (Querstret & Cropley, 2013;Watkins et al, 2007), which are easier to modify than facets of personality (Magidson, Roberts, Collado-Rodriguez, & Lejuez, 2014). Though less consistently linked to distress, psychopathology, and other negative outcomes than the brooding component of depressive rumination (e.g., Johnson et al, 2016;Rogers & Joiner, 2018;Treynor et al, 2003), the salubrious effect of self-reflection observed in this study suggests a potential adaptive value of self-focused attention. To wit, our finding ruminative response inhibition among those with high self-reflection tendencies, in particular within a negative interpersonal context, is consistent with others observing a positive association between self-reflection and interpersonal effectiveness (Takano, Sakamoto, & Tanno, 2011).…”
Section: Discussionmentioning
confidence: 56%
“…This possibility is evidenced by the high percentage of individuals with a previous suicide attempt in our sample (i.e., 22.79%). Evidence suggests that many risk factors demonstrate a stronger relationship with suicidal ideation at higher levels of ideation, with perceived burdensomeness exhibiting a particularly strong relationship with suicidal ideation at higher levels of suicidal ideation (Rogers & Joiner, 2017). Thus, if our sample had included more individuals with less severe suicidal symptoms, the relationship between perceived burdensomeness and DT suicide risk may have been even more comparable to the relationship observed in previous research (Chu et al, 2017).…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, some of the participants we included in the current study overlap with other studies. Although some of these INQ data were used in 12 other publications (Anestis et al, 2018; Chu et al, 2017b; Hagan, Podlogar, Chu, & Joiner, 2015; Hames et al, 2015; Hawkins et al, 2014; Hom, Hames, et al, 2017; Rogers et al, 2017a; Rogers et al, 2017b; Rogers et al, 2018; Rogers & Joiner, 2016, 2018; Silva, Ribeiro, & Joiner, 2015), it should be noted that our participants’ data do not overlap with those used in primary 15-item INQ validation paper (Van Orden et al, 2012). Furthermore, the analyses that we conducted are unique to the current study and provide important clinical utility information with the most up-to-date data.…”
Section: Methodsmentioning
confidence: 99%